2014
DOI: 10.1063/1.4891197
|View full text |Cite
|
Sign up to set email alerts
|

High-Tc Phase of PrO0.5F0.5BiS2 single crystal induced by uniaxial pressure

Abstract: We demonstrated a pressure-induced phase transition from a low-T c phase (3.5 K) to a high-T c phase (8.7 K) in single crystalline PrO 0.5 F 0.5 BiS 2 . The high-T c phase is easily observed even at 0.7 GPa by uniaxial pressure obtained from a geometric effect of a single crystal with an extremely-thin thickness. For this phase transition, superconducting anisotropy and the coherence length along the c axis change from γ = 20 to 9.3 and from ξ c = 0.56 to 0.71 nm respectively. It is suggested that a shrinkage … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 19 publications
0
27
1
Order By: Relevance
“…Interestingly, in a theoretical study, an insulator to metal transition under pressure along with superconductivity at low temperatures has been suggested for the LaO 0.5 F 0.5 BiS 2 compound [28]. Further, worth mentioning is the fact that in a recent study the impact of hydrostatic pressure on transport properties of single crystalline PrO 0.5 F 0.5 BiS 2 resulted in semiconducting to metallic behavior [29]. It is shown that under pressure the high superconducting transition temperature (T c ) phase forms in the compound and that is metallic.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, in a theoretical study, an insulator to metal transition under pressure along with superconductivity at low temperatures has been suggested for the LaO 0.5 F 0.5 BiS 2 compound [28]. Further, worth mentioning is the fact that in a recent study the impact of hydrostatic pressure on transport properties of single crystalline PrO 0.5 F 0.5 BiS 2 resulted in semiconducting to metallic behavior [29]. It is shown that under pressure the high superconducting transition temperature (T c ) phase forms in the compound and that is metallic.…”
Section: Resultsmentioning
confidence: 97%
“…9 Superconductivity in LnO 1-x F x BiS 2 with Ln = Ce, Pr, Nd and Yb also followed soon. [10][11][12][13][14][15][16] T c is enhanced by chemical pressure [18][19][20] or external applied pressure [22][23][24][25][26][27] as observed for LnOFeAs 28 for example in LnO 1-x F x BiS 2 , a slight enhancement in T c has been reported by substituting Se at the S sites or by inter-mixing rare earth ions. [18][19][20][21] Hole doping via alkali earthmetal-substitution at Ln-site did not yield superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the T c increases up to around 6.5 K when the samples are measured under a high pressure [27]. This increase of T c is common properties in BiS 2 compounds with the block layers of LnO (Ln=La, Pr, Ce, Nd) [28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…This effect may be related to the enhancement of T c . Actually, many papers have revealed that T c of BiS 2 based superconductors with LnOBiS 2 type structure increases under the high-pressure where the lattice constant decreases [27][28][29][30][31][32][33][34][35][36]. Theoretical study also reported that the band structure of BiS 2 -based materials is sensitive to the lattice constant along the c axis [37,41,42].…”
mentioning
confidence: 99%